2004
DOI: 10.1007/s00253-003-1440-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ask?asd operon in aminoethoxyvinylglycine-producing Streptomyce s sp. NRRL 5331

Abstract: The first two genes of the threonine pathway, ask and asd, were cloned and sequenced from the aminoethoxyvinylglycine-producing Streptomyces sp. NRRL 5331. The two genes are organized in a bicistronic operon. ask, encoding the apartokinase (ASK), is located upstream from asd. The presence of a ribosome-binding site within the ask sequence suggests that this open reading frame encodes two overlapping proteins. The formation of both subunits of the aspartokinase from a single gene was studied using antibodies ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The nested α-and β-subunits of AKs, which were originally discovered in Bacillus subtilis, 22 can be found in most Gram-positive bacteria, including mycobacteria, 33 Corynebacterium bacteria, 23,34 Amycolatopsis mediterranei 35 and Streptomyces bacteria. 36 Recent structural studies 37 have suggested that in the AK from Corynebacterium glutamicum, the nested truncated β-subunit is required for controlling feedback inhibition by the pathway endproducts threonine and lysine, possibly through structural changes in the α 2 β 2 -quaternary structure upon effector molecule binding. The catalytic AK active centre resides on the N-terminal part of the α-subunit, which is missing from the β-isoform, and it has been suggested that in the presence of threonine and lysine, the β-subunit prevents access of the substrate to the active site on the α-subunit.…”
Section: Closing Remarksmentioning
confidence: 99%
“…The nested α-and β-subunits of AKs, which were originally discovered in Bacillus subtilis, 22 can be found in most Gram-positive bacteria, including mycobacteria, 33 Corynebacterium bacteria, 23,34 Amycolatopsis mediterranei 35 and Streptomyces bacteria. 36 Recent structural studies 37 have suggested that in the AK from Corynebacterium glutamicum, the nested truncated β-subunit is required for controlling feedback inhibition by the pathway endproducts threonine and lysine, possibly through structural changes in the α 2 β 2 -quaternary structure upon effector molecule binding. The catalytic AK active centre resides on the N-terminal part of the α-subunit, which is missing from the β-isoform, and it has been suggested that in the presence of threonine and lysine, the β-subunit prevents access of the substrate to the active site on the α-subunit.…”
Section: Closing Remarksmentioning
confidence: 99%
“…We previously reported the identification of a 13-kb chromosomal region involved in FVG production based on the analysis of Tn5 insertion libraries in P. fluorescens WH6 (Halgren et al, 2013;Kimbrel et al, 2010). This gene cluster is distinct from those involved in the production of other oxyvinylglycines (Cuadrado et al, 2004;Rojas Murcia et al, 2015;Yasuta et al, 2001), which vary considerably despite conserved structural features of the molecules. The objectives of the current study were to: 1) systematically interrogate each gene within the 13-kb region to define the gvg cluster, and 2) investigate the transcriptional organization of the gene cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the biosynthetic pathway of FVG using comparative genomics or other tools is difficult because the known biosynthetic pathways of oxyvinylglycines vary considerably (Cuadrado et al, 2004;Rojas Murcia et al, 2015;Yasuta et al, 2001) and because FVG has an unusual aminooxy linkage (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The FVG analog aminoethoxyvinylglycine (AVG) is produced by Streptomyces sp. strain NRRL 5331 (33) and is structurally similar to FVG. Like FVG, AVG also inhibits the germination of grasses and is antagonistic toward E. amylovora (27,28).…”
mentioning
confidence: 98%